DEGRADASI KOLESTEROL DAN KOPROSTANOL DALAM SEDIMEN SUNGAI - Suprihatin, Iryanti Eka (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010, 2012)
Cholesterol and other steroid compounds like coprostanol, epicoprostanol, have been used as source indicator for fecal pollution in aquatic environments. This is because of the unique steroid composition of animal feces. To determine the source of fecal pollution, the ratios of steroid compounds in the sample are used. Thus any reaction or changes to any steroid compound in the environment will affect the determination. In this paper a study on the interconversion of cholesterol and coprostanol in river sediments is reported. The study suggests that there is no such changes that any steroid compounds detected in a sediment sample will show their primary sources. This implies that the composition or ratio of the compounds can be used as source indicator for fecal pollution. The study also found that both cholesterol and coprostanol degradation are first order with rate constants of 0,063[kolesterol]mgL-1day-1 and 0.045[kop]t mgL-1day-1 respectively.
Keywords: kolesterol, koprostanol, degradasi, aerob, steroid, feces